2009
DOI: 10.1105/tpc.109.069682
|View full text |Cite
|
Sign up to set email alerts
|

Replication Stress Leads to Genome Instabilities inArabidopsisDNA Polymerase Δ Mutants

Abstract: Impeded DNA replication or a deficiency of its control may critically threaten the genetic information of cells, possibly resulting in genome alterations, such as gross chromosomal translocations, microsatellite instabilities, or increased rates of homologous recombination (HR). We examined an Arabidopsis thaliana line derived from a forward genetic screen, which exhibits an elevated frequency of somatic HR. These HR events originate from replication stress in endoreduplicating cells caused by reduced expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 75 publications
4
50
0
Order By: Relevance
“…DNA Pol d is conserved in eukaryotes and is important in regulating genomic stability and development in Arabidopsis (Schuermann et al, 2009;Iglesias et al, 2015). To our knowledge, the biological functions of Arabidopsis POLD2 have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA Pol d is conserved in eukaryotes and is important in regulating genomic stability and development in Arabidopsis (Schuermann et al, 2009;Iglesias et al, 2015). To our knowledge, the biological functions of Arabidopsis POLD2 have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4E, many more GUS staining sectors were observed in the cotyledons in pold2-1 than in the wild type, suggesting that HR is negatively modulated by POLD2. A previous study indicated that mutations in the catalytic subunit of Pol d (POLD1) result in genome instability and enhance the frequency of somatic intramolecular HR (Schuermann et al, 2009). We also found that the telomere was shorter in pold2-1 or pold2-1 dms3-4 than in the wild type or dms3-4 (Fig.…”
Section: Map-based Cloning Of Pold2mentioning
confidence: 99%
“…We next focused on nrp1-1 nrp2-1 for more detailed analyses. To address whether the observed somatic HR defects are reproducible with different recombination substrates, the line 1445 containing a similar GUS reporter construct as in 1406 but at a different genome location (Fritsch et al, 2004;Schuermann et al, 2009) was introgressed into nrp1-1 nrp2-1 by crossing. Similar to 1406, 1445 also showed a reduction in somatic HR in the nrp1-1 nrp2-1 mutant background compared with Col under either standard growth conditions or UV treatment (Figure 2A).…”
Section: Nrp1 and Nrp2 Are Required For Both Intramolecular And Intermentioning
confidence: 99%
“…The two fragments contain an overlapping region and are spatially arranged as inverted repeats that restore a functional GUS after an HR event ( Figure 1A; Schuermann et al, 2009). The restored GUS activity can be visualized in planta as a blue spot/sector by histochemical staining ( Figure 1B).…”
Section: Depletion Of Nap1s or Nrps Reduces Somatic Hrmentioning
confidence: 99%
See 1 more Smart Citation